A review for non-antibiotic treatment of Helicobacter pylori: new insight - Shadvar, Neda; Akrami, Sousan; Mousavi Sagharchi, Seyyed-Mohammad-Amin; Askandar, Rafee Habib; Merati, Alireza; Aghayari, Masoomeh; Kaviani, Nikki; Afkhami, Hamed; Kashfi, Mojtaba (Frontiers in Microbiology, 2024)
Gastric ulcers and gastric cancer are brought on by the Helicobacter pylori bacteria, which colonizes under the stomach mucous membrane. Different medication regimens are used to remove it, but the illness returns and becomes more resistant, which lowers the treatment rates.Additionally, this bacterium now exhibits a skyrocketing level of multi-drug resistance, necessitating recurrent therapeutic treatments. The negative effects of synthetic medications in comparison to conventional therapies are another significant factor in favor of nonpharmacological therapy. The most significant side effects of popular anti-gastric ulcer medications include nausea, vomiting, and diarrhea. Stomach ulcers have previously been treated with herbal remedies and complementary treatments like probiotics.When probiotics are ingested, the host experiences several advantages that may be brought about by altering the bacterial flora in the digestive system. Additionally, stronger-acting chemical compounds and plant extracts can be employed to treat patients. In this article, we look at the substances and medications that are utilized in place of synthetic stomach ulcercuring treatments.